Seroprevalence of Hepatitis B virus infection among blood donors in Shia Muslims in a population of Lucknow (Bangladesh Journal of Medical Science, 2013)
Background: The objective of this study was to determine the prevalence and trends in hepatitis B infection among blood donors Shia Muslims attending the blood bank in Era's Lucknow Medical College lucknow. A retrospective study was carried out by reviewing the results of HBsAg among blood donors for the years 2002 to 2012. During this period,11962 blood donors were studied. Conclusion: There is a constant need to improve public awareness programs to lower the incidence of hepatitis B infection in the general population and in Shia Muslims and consequently first time blood donors. Future studies are also required to determine the trends and outcomes of these programs. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 146-149 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14942